Consumer Trust: Perception and Satisfaction in Selected New Food Ventures - Gabriel, Jersey M. (RSF Conference Series: Business, Management and Social Sciences, 2025)
This quantitative study investigates the relationship between consumers’ perceptions, satisfaction, and trust in selected new food ventures. In a marketplace characterized by innovation, evolving food technologies, and increasing consumer awareness, establishing trust remains a critical challenge for emerging food businesses. The study aims to determine how perception and satisfaction influence trust toward food ventures operating for less than five years. Using a correlational research design, a validated questionnaire was distributed to 100 respondents through an online survey conducted between January and March 2025, achieving a 92% response rate. Data were analyzed using mean, standard deviation, and Spearman’s rank correlation through SPSS software. Findings revealed significant positive correlations between consumer perception, satisfaction, and trust, indicating that higher satisfaction and positive perception levels strengthen trust in emerging food ventures. The study highlights transparency, product quality, and ethical operations as pivotal in sustaining consumer trust and loyalty. These insights provide practical guidance for entrepreneurs and policymakers aiming to strengthen customer relationships and promote sustainable food business practices in the Philippines.